2004
DOI: 10.1161/01.cir.0000131518.25959.8f
|View full text |Cite
|
Sign up to set email alerts
|

Statins for Stroke Prevention

Abstract: Abstract-The occurrence of stroke increases with age, particularly affecting the older elderly, a population also at higher risk for coronary heart disease (CHD). Epidemiological and observational studies have not shown a clear association between cholesterol levels and all causes of stroke. Nonetheless, large, long-term statin trials in patients with established CHD or at high risk for CHD have shown that statins decrease stroke incidence in these populations. Combined data from 9 trials including 70 070 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 75 publications
2
40
0
1
Order By: Relevance
“…Despite the link between low cholesterol and ICH, statin therapy has increased ICH risk in clinical trials, 38 but did not increase risk in other reports. 39 The relation between smoking and ICH tends to be weak and inconsistent in individual studies. In a meta-analysis, 3 the relative risk of ICH from current smoking versus never smoking was 1.31 (95% CI 1.09 to 1.58).…”
Section: Sturgeon Et Al Risk Factors For Intracerebral Hemorrhagementioning
confidence: 99%
“…Despite the link between low cholesterol and ICH, statin therapy has increased ICH risk in clinical trials, 38 but did not increase risk in other reports. 39 The relation between smoking and ICH tends to be weak and inconsistent in individual studies. In a meta-analysis, 3 the relative risk of ICH from current smoking versus never smoking was 1.31 (95% CI 1.09 to 1.58).…”
Section: Sturgeon Et Al Risk Factors For Intracerebral Hemorrhagementioning
confidence: 99%
“…Although hypercholesterolemia is associated with carotid arterial disease and coronary heart disease, its role in the pathogenesis of stroke is unclear. [1][2][3] Several cohort studies have shown little or no positive correlation between the incidence of stroke and increased levels of serum cholesterol. 4,5 Some 6 -9 but not all 10,11 intervention studies of 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) have indicated beneficial effects of lowering cholesterol levels in reducing the risk of stroke.…”
mentioning
confidence: 99%
“…6,7 Similarly, higher cholesterol levels are associated with an increased risk of ischemic stroke, and treatment with statins leads to a RR reduction of approximately 20%. 42 Anticoagulation remains the mainstay of preventing risk of stroke and TIA in patients with AF. While warfarin is highly effective, the emergence of newer antithrombotic agents and left atrial appendage closure devices may offer alternative therapeutic strategies for stroke prevention in patients with AF without the need for regular monitoring.…”
Section: Therapeutic Strategies For Prevention and Treatment Of Strokementioning
confidence: 99%